The effects of the compensation system on job satisfaction and turnover intention of employees in the Republic of Serbia - Jevtić Tamara; Gašić Dimitrije (Strategic Management)
Background: The motivation for researching the effects of the compensation system on job satisfaction and the turnover intentions, as well as the mediating role of job satisfaction between the compensation system and the turnover intention, was due to the insufficient number of studies of the proposed model in the Republic of Serbia. Purpose: refers to the review of theoretical and empirical knowledge so far, the creation of a conceptual framework and the implementation of the analysis itself on the collected sample with the aim of determining the effects of influence on the mentioned variables and giving recommendations to employers on how they can positively influence job satisfaction and reduce turnover intentions. Methodology: consists of theoretical and empirical research. The theoretical part refers to the review of previous research by other authors who examined the effects of the displayed variables based on which the conceptual framework of the research was set. The empirical part refers to conducting an analysis on a sample of 100 employees in the Republic of Serbia. The analysis was carried out using the Partial least squares structural equation modelling (PLS-SEM) method, using the SmartPLS software. Findings: the main findings of the research indicated that there are direct positive effects of the compensation system on job satisfaction and turnover intention, and that job satisfaction has an indirect effect on the relationship between the compensation system and the turnover intention of employees. Limitations: refer to the small number of respondents as well as the insufficient number of research in the Republic of Serbia within the proposed model. Recommendations for future research refer to collecting a larger number of respondents as well as determining the effects on other attitudes such as work engagement, employee commitment and employee behaviour such as innovative work behaviour and employee performance.